Comparison effecting of mixture on three meat factors and three culinary sectors on consumers in restaurant Nusa Dua - Suarta, Gede; Sukada, Ketut; Suberata, Wayan (International research journal of management, IT and social sciences, 2020)
This study aims to find the best culinary mix of 3 meat factors, namely: chicken, pork, and beef mixed with 3 culinary factors, namely kebab, spaghetti, and hamburger. The research design used a factorial design with 3 replications, so that the total number of observations was 27 units including KA (chicken kebab), KB (pork kebab), KS (Cow Kebab), SA (Chicken Spaghetti, SB (Spaghetti Babi, SS (Spaghetti) Cow, HA (Chicken Hamberger), HB (Pig Hamberger, HS (Cow Hamberger) each repeated 3 times so that a 3x3x3 factorial analysis occurs using analysis of variants processed with SPSS (Statistical Product System Solution), each variable is measured by the number of consumers who From the results of the Duncant Test, it was found that the culinary products that bought the most buyers were 37.56 (P<0.05), spaghetti 23.22 (P<0.05), hamberger 21.11 (P<0.5), while the desire to choose a mixture of meat was not significantly different, chicken was 31.67 (P> 0.05, beef 21.11 (P>0.05), pork was 23.11 (P> 0,05) The interaction between culinary types and meat types was not significantly different (P> 0.05) It can be concluded that the real type of kebab culinary is the most preferred by consumers.